Evaluation of the mating disruption technique on Tecia solanivora Povolny (Lepidoptera: Gelechiidae) - BOSA, FELIPE; WITZGALL, PETER; COTES, ALBA M.; FUKUMOTO, TAKEHIKO; BARRETO, NANCY (Revista Colombiana de Entomología, 2005)
One of the promising applications of pheromones is their use to control insects through mating disruption, in which multiple pheromone sources are created at high concentrations to produce male confusion, masking female pheromone detection and disrupting mating. In order to evaluate this technique for Tecia solanivora control, dispensers formulated with a pheromone blend were deployed in the field and in potato storage conditions. When adult male populations were monitored under field conditions, 39 males were caught in the area treated with pheromone dispensers, compared to 1593 males in the untreated area. Under storage conditions 39% of damage incidence and 100% of severity in tubers were observed in untreated storage rooms, compared to 9% of incidence and lower severity in rooms treated with pheromone dispensers.